Studi Penambahan Inhibitor Organik Ekstrak Daun Bawang Tiwai (Eleutherine americana Merr.) pada Baja API 5L dalam Lingkungan 3,5% NaCl - Triana, Yunita; Rinda, Sari Shaimah; Jatmoko, Awali; Sulistijono, Sulistijono (SPECTA Journal of Technology, 2018)
One that can be used as an organic inhibitor is bawang tiwai leaves extract. This study used 3.5% NaCl as corrosive media with inhibitor concentration of bawang tiwai leaves extract from 0 ppm to 500 ppm and immersion time from 10 days up to 30 days. The efficiency of inhibition was measured using a weight loss corrosion test, while the corrosion rate was obtained from polarization measurements. The FTIR test results show that the extract contains flavonoid compounds that act as antioxidants and inhibit corrosion. Inhibitory efficiency achieved up to 95.4545% for the addition of 300 ppm inhibitor and 20 days of immersion time. This inhibitory behavior is also supported by polarization measurements where the lowest corrosion rate of 0.00128 mm/year is obtained at the same concentration and immersion time.